Modeling and simulation of HVRT and LVRT enhancement capability for doubly fed induction generator based wind energy conversion system - P, Srinivasan; Samiappan, Dhandapani (International Journal of Engineering and Technology, 2018)
Generation of power using wind turbine is more across the globe, but a problem related using wind method of power generation is volt-age variation across the grid. The performance of wind turbine goes below the specified level during grid voltage variation. It might be due to overvoltage or under voltage condition. Under voltage capability of WECS is called to be LVRT i.e. Low Voltage Ride Through and over voltage or high voltage capability of WECS is called High Voltage Ride Through (HVRT). Due to unfortunate grid voltage variation the converters connected to wind turbines are affected hence these devices needs to be prevented from lowering of voltage and increase in voltage. Therefore an algorithm is been developed to overcome LVRT and HVRT effects and to protect DFIG under this condition without distressing its routine. Simulation results and system modeling shows that effectiveness under various operating con-dition.Â
Keywords: WECS; LVRT; HVRT; Grid Code and Power Converters.